Fenestra coeli. The Virgin Mary Symbolized as the Window of Heaven in Images of the Annunciation - Salvador-Gonzalez, José María (Biblica et Patristica Thoruniensia, 2025)
This article aims two main objectives. First, it intends to shed light on how the metaphor “window of heaven” (fenestra coeli) applied to the Virgin Mary translates the doctrinal meaning of her virginal divine motherhood. Second, it seeks to demonstrate that the circumstance that in some paintings of the Annunciation a window is crossed by a ray of light metaphorizes the virginal conception and the supernatural birth of God the Son incarnated as a man in Mary’s spotless womb. To achieve these objectives, we will use a double series of comparative analyses as methodological resources: first of all, we will expose many texts by Church Fathers, theologians, and liturgical hymnographers that allude to Mary as a window of heaven; then we will consider eleven paintings of the Annunciation in which the ray of light coming from God the Father passes through a window before reaching the Virgin. By relating these texts and these images, we can conclude that the proposed objectives are met with good logic.